Geology of Planina pri Jezeru and its environs (Slovenia) - Mihael Brenčič; Nina Rman (Geologija, 2008)
The article describes the results of detailed geological mapping of the wider environs of Planina pri Jezeru north of Bohinj. In the literature the Upper Triassic massive and bedded limestone, Jurassic limestone, Cretaceous clastic rocks and Pleistocene sediments have been reported in this area up to now. The article supplements existing lithostratigraphic information by defining exact locations of the Pleistocene sediments at Planina pri Jezeru and Planina v Lazu, and of Jurassic rocks. In Poljane a Neptunian dyke and bioclastic limestone, while north of Mizčna glava a flat-bedded microsparitic limestone were described for the first time.Correlation to the Triglav Lakes Valley Jurassic beds indicates equivalent facieses. Allochthon Cretaceous biocalcarenite and jasper situated east of Planina pri Jezeru are also described due to their importance for further glaciological studies. The results show that the recent lake Jezero na Planini pri Jezeru is formed due to the accumulation of Pleistocene glacial-lacustrine fine-grained sediment in till,deposited on the Dachstein limestone.